PENGARUH RELATIONSHIP MARKETING DAN BRAND IMAGE TERHADAP LOYALITAS KONSUMEN PADA HOTEL WINSTAR PEKANBARU - Nur Sohana; Meyzi Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was conducted at the Winstar Hotel Pekanbaru, Jl.Moh.Ali, No.118, Padang Terubuk, Kec.Senapelan, Pekanbaru.  This study aims to determine the effect of relationship marketing and brand image on customer loyalty partially and simultaneously.  This study uses a quantitative descriptive analysis method with the SPSS program. The population in this research is all consumers who  purchases services at the winstar hotel pekanbaru in 2019 were 14.401 and the sample from this study were 100 respondents from the winstar hotel pekanbaru consumers.The Determination of the sample in this study used the Slovin formula, namely non-probability sampling technique with purposive sampling technique.            Data analysis using validity test, reliability test, simple linear analysis, multiple linear analysis, determination analysis and significance test with t test (partial test) F test (simultaneous test).  The results of this study show the result of the relationship marketing t-test hypothesis on customer loyalty, namely t count (14,095)> t table (1,660),  means relationship marketing has a  significant effect on  consumer  loyalty.  Second, brand image on consumer loyalty is t count (14,206)> t table (1,660), meaning that brand image has a significant effect on customer loyalty.  F test results relationship marketing and brand image have a significant effect on customer loyalty, namely F count (119,317)> F table (3.09).Keywords: Relationship Marketing, Brand Image, Consumer Loyalty